Is transit oriented development reducing activity spaces? - Olaru, D.; Curtis, Carey (World Conference on Transport Research Society, 2007)
This paper reports on the potential mobility effects arising from the construction of a new suburban railway running 72 kms through Perth's southern suburbs and the corresponding transit oriented development (TOD). The aim of the research is to measure the degree to which the TOD opportunity leads residents to reduce their car travel and to substitute this with public transport. In this particular paper we investigate the potential modification (reduction) of the activity spaces resulting from TOD and the relationship with location preferences. Work and non-work activities in the neighbourhood are analysed together with physical activity (including cycling and walking). The activity spaces are analysed across 5, 10, 15 walk and 5 in drive isochrone areas and in conjunction with socio-demographic characteristics of the areas. We compare the behaviour of residents living in four travel zones within one railway station precinct (Bull Creek precinct - a significant generator of trips) located along the new railway.Our research findings show that workplace and school are significant 'pegs' of activity spaces, outlining their size and shape. The second moments and confidence ellipses tend to decrease in size with distance from the railway station, as a result of the socio-deomographic profile of the areas. The dominance of commuting in the travel of households located in the 5 and 10 min walking areas influences the spatial extension of the activity spaces. Areas further from the railway station are characterised by a signficantly higher number of family members, and especially school age children. Their activity spaces are strongly related to the location of schools. After commuting was accounted for, the activity spaces in all travel zones shrunk considerably, almost 'mirroring' the neighbourhood area. Summarising, the distance from the railway station and urban features seemed to play a minor role onto activity spaces; on the other hand, family size and car availability have had significant impact on the activity engagement and the size of the activity spaces. They were more strongly conditioned by the time constraints (institutional or personal) compared to the accessibility provided by the transport network.